2019
DOI: 10.1088/1757-899x/609/3/032044
|View full text |Cite
|
Sign up to set email alerts
|

Performance of mechanical filters used in general ventilation against nanoparticles

Abstract: Filtration is a simple and effective way to capture particles of different sizes. According to ANSI/ASHRAE 52.2 standard, ventilation filters efficiency is tested for particles ranging from 0.3 to 10.0 μm. To our knowledge, performances of entire filters for nanoparticles are still very limited and particle size of 300 nm is commonly used as the Most Particle Penetration Size (for mechanical media). In order to evaluate the filter performance for nanoparticles, five type of filters (from MERV 8 to HEPA) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…First, in our former study, the measurements were taken at an aerosol diameter of 0.5 μm [10]. At that particle size, leakage through the filtration material of the respective face coverings is known to be very high [13]. e viral aerosol used in this study had a different particle size distribution (Figure 1(a)) compared to our former study.…”
Section: Discussionmentioning
confidence: 83%
“…First, in our former study, the measurements were taken at an aerosol diameter of 0.5 μm [10]. At that particle size, leakage through the filtration material of the respective face coverings is known to be very high [13]. e viral aerosol used in this study had a different particle size distribution (Figure 1(a)) compared to our former study.…”
Section: Discussionmentioning
confidence: 83%
“…Brochot et al 38 explored the most penetrating particle size of different commercial filters and found that the 150–500 nm range provides a better estimation of the MPPS in size range of 20–500 nm. Hanley et al 24 found that a minimum filtration efficiency often occurred in the 0.1–0.5 μm diameter size range.…”
Section: Resultsmentioning
confidence: 99%
“…theoretical efficiency predicts the most penetrating particle size occurs around 0.3 μm, it is reported that smaller particles may show the lowest removal efficiency at a higher velocity. 37 Brochot et al 38 explored the most penetrating particle size of different commercial filters and found that the 150-500 nm range provides a better estimation of the MPPS in size range of 20-500 nm.…”
Section: Particle Size Removal Efficiencies Of Filtersmentioning
confidence: 99%
“… 21 , 22 In addition, 0.3 µm allows for a worst-case evaluation of filtration approaches as this is the most penetrating particle size for N95 respiratory masks and corresponds to MERV (Minimum Efficiency Reporting Value) criteria for HVAC (Heating, Ventilation, and Air Conditioning) filter media which can vary within a range of 150 to 500 nm depending on particles’ shape, charge, or relative humidity. 23 …”
Section: Methodsmentioning
confidence: 99%